IMAGENS DE SI NA PEÇA PUBLICITÁRIA OBRA DE ARTE, DE COCA-COLA (REMUNOM, 2024)
This article aims to analyze the discourse engendered in an advertising for the Coca-Cola brand, aiming to verify how the meaning effects are engendered in an advertisement for this brand, which mobilizes a large part of food products (in the of soft drinks and juices) in Brazil. For this analytical procedure, Discourse Analysis is used as a theoretical and methodological tool, specifically the concepts of enunciation scenes developed by Dominique Maingueneau, namely, encompassing scene, generic scene, scenography and ethos. The corpus to be analyzed comprises an advertisement for the Coca-Cola brand, entitled 'Work of Art', widely disseminated by the Coca-Cola channel on YouTube, on March 7, 2023. As it is a famous brand, the advertisements have a large circulation, affecting both spectators and meaning, making the discursive analysis of their advertisements relevant. As a result, at the end of this analytical journey, the possible contributions to understanding the discursive functioning of advertising pieces as catalysts for the “good image” of companies concerned with culture and art are weighed.